Antibacterial Activity of Sumbawa Forest Honey (Apis dorsata) against Klebsiella pneumoniae ATCC BA1705 - Untari, Lania Pradiva; Wardoyo, Eustachius Hagni; Dirja, Bayu Tirta (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2025)
Klebsiella pneumoniae is an opportunistic bacterium often associated with antibiotic resistance, necessitating the investigation of natural antibacterial alternatives. Honey is recognized for its bioactive ingredients that possess antibacterial properties. This research sought to assess the antibacterial efficacy of Sumbawa forest honey (Apis dorsata) against K. pneumoniae ATCC BA1705 by inhibition zone test. A laboratory experiment was performed using the well diffusion technique. K. pneumoniae suspensions (McFarland 0.5) were injected onto Mueller Hinton Agar. Wells (Ø 6 mm) were filled with 100 µL of honey at concentrations of 25%, 50%, 75%, and 100%. Tetracycline (1 µg/µL) acted as the positive control, while distilled water functioned as the negative control. Plates were incubated at 35±2°C for a duration of 18 to 24 hours. Inhibition zones were quantified using a caliper, and each experiment was conducted in sextuplicate. Data were expressed as mean ± standard deviation. No inhibitory zones were found at 25% and 50% concentrations (0 mm). Antibacterial activity was seen at 75% concentration, yielding a mean diameter of 10.33±SD mm, and raised to 100% concentration, resulting in a mean diameter of 11.33±SD mm. Tetracycline generated a 26 mm inhibitory zone, while distilled water exhibited none (0 mm). The conclusion is Sumbawa forest honey exhibits concentration-dependent antibacterial activity against K. pneumoniae, with moderate inhibition at concentrations ≥75%. Although less effective than tetracycline, these findings support the potential role of honey as a complementary antibacterial agent.